2014
DOI: 10.1111/cen.12616
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of serum lipid profiles and bone mineral density in postmenopausal Chinese women

Abstract: In Chinese postmenopausal women, elevated levels of serum HDL-C had a greater probability of being osteoporosis than the lower HDL-C levels. Our analysis showed higher HDL-C level that is favourable for cardiovascular diseases should be regarded as a risk factor for osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 37 publications
1
44
2
Order By: Relevance
“… 38 , 41 In some studies, serum TG and HDL-C were found to be correlated with BMD, but no relationship was seen between either TC or LDL-C and BMD. 42 44 Li et al 44 only focused on the postmenopausal Chinese women; however, our studies focused on both men and women aged 40–95 years old, where data on this population are scarce. This is population-based and included a relatively large sample size.…”
Section: Discussionmentioning
confidence: 98%
“… 38 , 41 In some studies, serum TG and HDL-C were found to be correlated with BMD, but no relationship was seen between either TC or LDL-C and BMD. 42 44 Li et al 44 only focused on the postmenopausal Chinese women; however, our studies focused on both men and women aged 40–95 years old, where data on this population are scarce. This is population-based and included a relatively large sample size.…”
Section: Discussionmentioning
confidence: 98%
“…Somehow, HDL-C showed a weak relationship with BMD (β = 0.151, P = 0.034). Since a latest report has determined some effects of HDL-C on bone fragility 32 ; and D’Amelio et al also suggested that HDL was significantly higher in osteoporotic patients than controls, the level of HDL could be used as screening for postmenopausal osteoporosis 33 . However, the exact relationship requires further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial data showed a negative association between BMD and serum TC, and LDL cholesterol ( 5 , 7 , 8 , 92 97 ). A few studies found no association and/or a positive association with serum cholesterol and LDL cholesterol ( 98 101 ). The summarized data from all the studies indicate that there is an existence of an inconsistent relationship for the case of HDL cholesterol and BMD ( 6 , 99 , 100 , 102 ).…”
Section: Discussionmentioning
confidence: 99%